The Effect of Loyalty on the Performance of Pharmaceutical Personnel in the Local Hospitals of the Special Region of Yogyakarta - Orbayinah, Salmah; Utami, Pinasti; Budi, Yunanda; Bilqis, Zulfa Muthia (Universitas Pahlawan, 2025)
Pharmaceutical personnel, as part of the healthcare workforce, are required to demonstrate strong performance because it directly influences the quality of services delivered to patients. Numerous studies have indicated that employee performance is closely linked to their level of loyalty. Therefore, this study was conducted to investigate how personnel loyalty influences their performance in providing patient care services. Aim: The purpose of this research is to examine the impact of employee loyalty—reflected through commitment, dedication, and engagement toward the organization—on the quality and efficiency of health services. Higher loyalty is expected to encourage medical and supporting staff to work more effectively, provide better attention to patients, and enhance overall patient satisfaction. This study also explores several factors that shape employee loyalty, including work environment, reward systems, and career development opportunities, and how these elements contribute to service quality. This research employed a non-experimental observational design with a cross-sectional approach and was carried out in the Special Region of Yogyakarta from September to December 2020. A total of 180 pharmaceutical personnel from five local hospitals participated as respondents. The instruments used were adapted from prior research, specifically the Organizational Commitment Questionnaire to measure loyalty and the Job Performance Questionnaire to assess personnel performance. Loyalty and performance levels were analyzed using descriptive statistics, while the influence of loyalty on performance was examined using Pearson-correlation analysis. The findings revealed a correlation coefficient of 0.732 with a significance level of 0.000, indicating a strong, positive, and statistically significant relationship. The study concludes that pharmaceutical personnel loyalty plays a substantial role in enhancing their performance in delivering healthcare services to patients.